Social Entrepreneurship Practice in Malaysia - The Case of Social NGO - Fakhrul Anwar, Zainol; Wan Norhayate, Wan Daud; Zulhamri, Abdullah; Mohd Rafi, Yaacob (2014)
This study scrutinises innovation, proactiveness and risk taking as indicators of effectiveness of a social NGO within the context of urban poverty, using Global Outreach as a case. This study begins with the introduction of brief background of organisation. Later,innovation, proactiveness and risk taking which are the gists of the content of the paper are discussed at length. As far as this case study is concerned, Global Outreach is effective enough. Capitasing on amended model of Grameen's model to suit needs and wants of urban poors, Global Outreach implies innovation, this is achieved because of proactiveness of staff. At the same time the ability of the organisation to deal with risk taking is verified. Organisational effectiveness of Global Outreach is well demonstrated when it able address urban poverty-almost 70 per cent of women borrowers are above the poverty line